2023
DOI: 10.1101/2023.01.15.524085
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cross-Species Protection to Innate Immunity Mediated by A Bacterial Pigment

Abstract: Bacterial infections are often polymicrobial.Pseudomonas aeruginosaandStaphylococcus aureuscause chronic co-infections, which are more problematic than mono-species infections. We found that the production ofS. aureusmembrane-bound pigment staphyloxanthin (STX), was induced by theP. aeruginosaexoproduct, 2-heptyl-4-hydroxyquinoline N-oxide (HQNO). The induction phenotype was conserved inP. aeruginosaandS. aureusclinical isolates examined. When subjected to hydrogen peroxide or human neutrophils,P. aeruginosasu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…A recent report showed that S. aureus inactivated the P. aeruginosa-derived siderophore pyochelin via the methyl-transferase Spm (staphylococcal pyochelin methyltransferase), increasing S. aureus survival during in vivo competition with P. aeruginosa in a murine wound co-infection model [114]. Furthermore, the secreted P. aeruginosa molecule HQNO induced the production of S. aureus membrane-bound pigment staphyloxanthin (STX), which consequently promotes resistance of both pathogens to innate immune effectors such as hydrogen peroxide [115].…”
Section: Interactions Observed In Wound Infection Modelsmentioning
confidence: 99%
“…A recent report showed that S. aureus inactivated the P. aeruginosa-derived siderophore pyochelin via the methyl-transferase Spm (staphylococcal pyochelin methyltransferase), increasing S. aureus survival during in vivo competition with P. aeruginosa in a murine wound co-infection model [114]. Furthermore, the secreted P. aeruginosa molecule HQNO induced the production of S. aureus membrane-bound pigment staphyloxanthin (STX), which consequently promotes resistance of both pathogens to innate immune effectors such as hydrogen peroxide [115].…”
Section: Interactions Observed In Wound Infection Modelsmentioning
confidence: 99%